Pengembangan Instrumen Deteksi Dini Perkembangan Kognitif Anak Usia 3 Tahun - Ati Sunarti; Heri Yusuf Muslihin; Dindin Abdul Muiz Lidinillah (Universitas Pendidikan Indonesia (UPI), 2023)
This study aims to determine the understanding and use of the instrument in detecting the cognitive development of children aged 3 years. The type of research used is Educational Design Research (EDR). The research model is the Reeves model, where this research was carried out with 2 trial stages. The subjects in this study were 9 participants, namely teachers, students and parents who have children aged 3 years. The instruments used are interview guidelines, documentation, expert validation, user validation and questionnaires. The research procedure consists of 4 stages, namely 1) problem identification and analysis, 2) product development and design, 3) product testing and reflection, and 4) maturing intervention and theoretical understanding. Penelitian ini bertujuan untuk mengetahui pemahaman dan penggunaan instrumen dalam mendeteksi perkembangan kognitif anak usia 3 tahun. Jenis penelitian yang digunakan yaitu Educational Design Research (EDR). Model penelitian nyaitu model Reeves, dimana penelitian ini dilakukan dengan 2 tahap uji coba. Subjek dalam penelitian ini adalah 9 orang pasrtisipan yaitu guru, mahasiswa dan orang tua yang memiliki anak usia 3 tahun. Instrumen yang digunakan yaitu pedoman wawancara, dokumentasi, validasi ahli, validasi pengguna dan kuisioner. Prosedur penelitiannya terdiri dari 4 tahap yaitu 1)identifiksi dan analisis masalah, 2) pengembangan dan desain produk, 3) uji coba produk dan refleksi, dan 4) maturing intervention dan theorical understanding.